Exploring time loyalty: The interweaving of time and loyalty in faculty administrator’s work strategies (Sociologisk Forskning, 2020)
Exploring time loyalty. The interweaving of time and loyalty in faculty administrator’s work strategiesThis article has an exploring and theorizing approach and aims to explore the function of the notion of time together with the concept of loyalty. The notion of acceleration of time and the new ”flexible” working life has created a duality where bureaucratic and administrative systems exist side by side with a more flexible organization, within which people can organize and plan their work themselves. That creates unregulated spaces, where administrators have to navigate and manage conflicting loyalties and uncertain responsibilities, creating further uncertainty, putting questions about one’s use of time and loyalties in focus. We explore this development by using the concept time loyalty and use that connection to analyze interviews with administrative staff within a university.This article concludes that there are ongoing negotiations regarding what to do, for whom, and when as well as legitimizing actions to justify fail responses to loyalty claims.
Keywords: Loyalty; Time; Symbolic interactionism; work-place relations; administration